Outdoor propagation prediction and measurement for WLAN application - Ishak, Saurdi (2006)
Propagation prediction and measurement plays an important role in the design and implementation of outdoor WLAN application. In this project, a threedimensional (3-D) ray tracing technique: Site Specific Outdoor / Indoor Propagation Prediction Code will be used to predict outdoor propagation effect in Tun Chancellor Hostel, University Technology Malaysia. Propagation prediction will be done within five blocks of building which area covers 215 X 235 meter consists of 11 locations receiver . The carrier frequencies are 2.4 GHz (IEEE 802.11b) and Patch antenna as a transmiter. Then measurements of signal strength using AirMagnet software will be carried out within the research area. 2 The objective of this project is to study on the losses of signal strength when it travels through Line of Sight (LOS) and effect on building (NLOS). Then do simulation of signal propagation and signal strength prediction at Tun chancellor Hostel (KTC) building and measurement of signal strength in determines places in KTC. In order to show the Propagation of signal the simulation code will be visualized using Matlab. The Airmagnet tool will be used for the measurements and results between simulations will be compared